Lessons Learned from Implementing a Rapid Test of a Technology Device in a Tertiary Hospital in Uganda - Pauline Byakika-Kibwika; Moses Muwonge; William Watts; Justine Kange; Raleigh Watts (Ubiquity Press, 2016)
Background: Many African hospitals participate in technology research studies that take many months or years. Fewer sites have experience with rapid studies, conducted over a period of weeks. Such studies can benefit the institution and its patients in the short term, and in the long term can help prepare the institution for adopting the new technology. Objectives: We conducted a rapid validation study of consumer fitness device at Mulago National Referral and Teaching Hospital in Kampala, Uganda. In doing so, we captured valuable lessons about how to conduct a rapid study that will be useful to future researchers conducting similar fast-paced studies. Methods: We conducted a descriptive study of a convenience sample of 57 patients. Patients who volunteered wore a fitness wristband device. Study staff collected vital signs using standard approaches. Findings: Our findings were as follows: (1) effective partnership by local experts can ensure success; (2) a PI with experience working with the hospital ethics committee is essential to a rapid study; (3) reassurance that the study design benefits patients and the institution can help speed approval; (4) conduct detailed assessment of patient population in advance; (5) allow sufficient time for logistics arrangements; (6) quickly pivot the approach as needed, consistent with the protocol; (7) conduct data quality review on every shift; (8) conduct a supplies inventory at the end of each shift; (9) make rapid decisions about hiring and discontinuing study staff; (10) implement a patient location protocol at the start of the study; and (11) ensure availability of study staff refreshments in the study room. Conclusion: A rapid study of innovative technology can be successful at a hospital in a resource-limited setting.